Anisakis physeteris Baylis ... - Muniz-Pereira, Luís C.; Vieira, Fabiano M.; Luque, José L. (Zenodo, 2009)
Anisakis physeteris Baylis Physeter macrocephalus Linnaeus, stomach, Rio de Janeiro (Pinto et al. 2004). Balaenoptera borealis Lesson, unspecified site of infection, unspecified locality (Pinto et al. 2004). ... : Published as part of Muniz-Pereira, Luís C., Vieira, Fabiano M. & Luque, José L., 2009, Checklist of helminth parasites of threatened vertebrate species from Brazil, pp. 1-45 in Zootaxa 2123 on page 5, DOI: 10.5281/zenodo.188170 ...